2011
DOI: 10.1016/j.cryobiol.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The unfolded protein response in human corneal endothelial cells following hypothermic storage: Implications of a novel stress pathway

Abstract: Human corneal endothelial cells (HCEC) have become increasingly important for a range of eye disease treatment therapies. Accordingly, a more detailed understanding of the processing and preservation associated stresses experienced by corneal cells might contribute to improved therapeutic outcomes. To this end, the unfolded protein response (UPR) pathway was investigated as a potential mediator of corneal cell death in response to hypothermic storage. Once preservation-induced failure had begun in HCECs stored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Further, the chemical modulators resveratrol and salubrinal were investigated to assess their impact on hMSC tolerance to hypothermic storage. These inhibitors were selected based on previous reports that demonstrated their differential roles as both protective and detrimental to cell viability and function in other cell systems[12]. Further, other investigations have also revealed that a single molecular modulator could have both a positive or negative effect on outcome which is specific to the cell type, storage temperature and medium[14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the chemical modulators resveratrol and salubrinal were investigated to assess their impact on hMSC tolerance to hypothermic storage. These inhibitors were selected based on previous reports that demonstrated their differential roles as both protective and detrimental to cell viability and function in other cell systems[12]. Further, other investigations have also revealed that a single molecular modulator could have both a positive or negative effect on outcome which is specific to the cell type, storage temperature and medium[14].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have now established that bioprocessing techniques are associated with the activation of molecular-based stress responses which contribute to cell loss during and following processing leading to failure[3,4,5,6,12,13,15,30,35]. These molecular responses can manifest as apoptosis or programmed cell death signaling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cell apoptosis induced by hypothermia/rewarming has been investigated extensively, especially for tissue preservation of major organs, such as liver or kidney tissues, there are still different opinions on whether cell death induced by hypothermia is through the mode of apoptosis [44] or necrosis [45]. Hence, the involvement of apoptosis in cold-induced cell death could not be excluded totally [43]; further characterization, perhaps using an apoptosis DNA fragment test, is needed to identify and confirm the mode of cell death. In addition, the final Vibration & cold storage effects on hMSC N. I.…”
Section: Mode Of Cell Death Induced By Vibration and Cold Storagementioning
confidence: 99%
“…However, annexin V expression is not exclusive to apoptotic cells as translocation of phosphatidylserine to the external cell surface also occurs during cell necrosis and oncosis [41,42]. Research into cold storage effects have shown that cold storage alone resulted in mainly necrosis [28,43]. Hence the observed increase of annexin Vþ and PIþ cell populations with prolonged cold storage duration could indicate more cells proceeding into cell death through oncotic necrosis (also referred to as swelling necrosis), a form of passive or accidental cell death.…”
Section: Mode Of Cell Death Induced By Vibration and Cold Storagementioning
confidence: 99%